2022
DOI: 10.21727/rpu.v13iespecial.3401
|View full text |Cite
|
Sign up to set email alerts
|

Enfermagem na Promoção da Saúde Mental de Adolescentes Escolares

Abstract: Introdução: Este artigo de revisão tem como objetivo identificar a literatura existente nas bases de dados selecionadas referente as estratégias utilizadas por enfermeiros na promoção da saúde mental de adolescentes na Atenção Primária à Saúde (APS). Materiais e Métodos: Revisão integrativa, onde identificou 6502 estudos, sendo 5056 na PubMed, 8429 na Web of Science, e 1417 na GALE. Após exclusão dos estudos duplicados e aplicação dos critérios de elegibilidade, foram selecionados 7 estudos. Resultados: Os 7 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
1
0
Order By: Relevance
“…With that in mind, due to the information obtained from the preliminary research, a shortage of studies described in the literature on the use of relational technologies in promoting the mental health of adolescent students was identified 10,11 . However, in the searches carried out in JBI Evidence Synthesis, in the Cochrane Database of Systematic Reviews, in Portal Periódicos Capes and in PROSPERO, no current and ongoing scope and systematic reviews on the subject were found.…”
Section: Introductionmentioning
confidence: 99%
“…With that in mind, due to the information obtained from the preliminary research, a shortage of studies described in the literature on the use of relational technologies in promoting the mental health of adolescent students was identified 10,11 . However, in the searches carried out in JBI Evidence Synthesis, in the Cochrane Database of Systematic Reviews, in Portal Periódicos Capes and in PROSPERO, no current and ongoing scope and systematic reviews on the subject were found.…”
Section: Introductionmentioning
confidence: 99%
“…Establishing a relationship between teachers, students and health professionals provides social support, whether emotional or informational [7,8,9]. However, there is still a lack of mental health promotion actions aimed at meeting the specific needs of school adolescents, as pointed out in studies described in the literature [10,11,12]. Given this context, the objective of this study was to carry out a systematic review to identify in the literature the strategies implemented in partnership with the primary care team that contribute to the promotion of mental health in school adolescents.…”
Section: Introductionmentioning
confidence: 99%